Dissecting the Genetic Basis of Resistance to Soybean Cyst Nematode Combining Linkage and Association Mapping. Issue 2 (1st July 2016) - Li, Ying‐hui; Shi, Xue‐hui; Li, Hui‐hui; Reif, Jochen C.; Wang, Jia‐jun; Liu, Zhang‐xiong; He, Sang; Yu, Bai‐shuang; Qiu, Li‐juan
Abstract : A set of 585 informative single‐nucleotide polymorphism (SNP) loci was used to genotype both a panel of diverse accessions and a set of recombinant inbred lines (RILs) bred from the cross Zhongpin03‐5373 (ZP; resistant to SCN) × Zhonghuang13 (ZH; susceptible). The SNP loci are mostly sited within genic sequence in regions of the soybean [ Glycine max (L.) Merr.] genome thought to harbor genes determining resistance to the soybean cyst nematode (SCN, Heterodera glycines Ichinohe). The three strongest quantitative trait nucleotides (QTNs) identified by association mapping (AM) involved the genes Glyma18 g02590 (a component of the multigene locus rhg1‐b ), Glyma11 g35820 and Glyma11 g35810 (an rhg1‐b paralog), as well as some other loci with smaller effects. The linkage mapping (LM) analysis performed using the RILs revealed two putative quantitative trait loci (QTL): one mapping to rhg1‐b and the other to an rhg1‐b paralog; both of these loci were also identified by AM. The former locus explained 25.5% of the phenotypic variance for SCN resistance and the latter 5.8%. In combination, the two major loci acted nonadditively, providing a high level of SCN resistance.